A history of the assessment of sex offenders : 1830-2020 - Laws, D. Richard (Emerald Publishing Limited, 2020)
Most forensic psychologists, psychiatrists and social workers involved in the assessment of sex offenders today have a good grasp of where the field stands. Many of their colleagues do not have an appreciation of why we are where we are. This book is an attempt to bridge that gap, to provide some historical background of sex offender assessment from 1830 to the present. Topics covered in this book include early efforts to identify and describe criminal populations statistically; the introduction of phrenology as a description of brain function; the efforts of criminal anthropologists to develop criminal taxonomies; the technology of anthropometry to identify individuals by measurement of bodily structure; and the introduction of fingerprinting which replaced anthropometry and remains largely unchanged to the present day. The guiding principle of the book is to help the reader understand that all of this represents a continuous thread of development and, disparate as they might seem, all of them are connected. This book is essential reading for undergraduates in psychology and sociology, as well as professionals in training and early stages of practice.
Includes index.
Keywords: Sex offenders -- History.; Criminal anthropology.; Sex offenders -- Psychology.; Social Science -- Criminology.; Crime & criminology.; elektronické knihy; electronic books